GAMBARAN TINDAKAN MENYIKAT GIGI PADA PASIEN USIA 15-64 TAHUN YANG BERKUNJUNG KE KLINIK GIGI RSUD LUBUK SIKAPING 2018 - Aljufri Aljufri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Indonesians who behave correctly in brushing their teeth are still very low, ie 7.3% in 2007 and 2.3% in 2013. This study aims to describe the action of brushing teeth in patients aged 15-64 years who visit to the dental clinic at Lubuk Sikaping Hospital. This type of research is descriptive with a population of all patients aged 15 years and 64 years who visited the dental clinic at Lubuk Sikaping Hospital. The research sample was 35 respondents with an accidental sampling method. Data collection is done by questionnaire. Data analysis is done univariately. The results showed an overview of the action of brushing teeth with criteria of both 2.86%, moderate 57.14%, and bad 14%. Based on sex, the number of female teeth brushing actions was obtained by criteria both 4%, moderate 68%, and bad 28%. Whereas for male respondents the criteria for either none, being 30%, and bad 70%. The conclusion of this study is that the picture of the act of brushing teeth for male respondents is mostly in the poor criteria and the female respondents are mostly in the criteria of being moderate. It is recommended for respondents to maintain healthy teeth and mouth by brushing their teeth 2 times a day after breakfast and the night before going to bed with the right brushing technique.